2020
DOI: 10.1002/asi.24401
|View full text |Cite
|
Sign up to set email alerts
|

Do new research issues attract more citations? A comparison between 25 Scopus subject categories

Abstract: Finding new ways to help researchers and administrators understand academic fields is an important task for information scientists. Given the importance of interdisciplinary research, it is essential to be aware of disciplinary differences in aspects of scholarship, such as the significance of recent changes in a field. This paper identifies potential changes in 25 subject categories through a term comparison of words in article titles, keywords and abstracts in 1 year compared to the previous 4 years. The sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The novelty together with the volume of publications attract other researchers' attention and increase visibility and impact (Tu & Seng, 2012). We have not studied novelty in this paper but Thelwall and Sud (2021) found that articles published around novel topics have a citation advantage using a word frequency analysis. It would be interesting to study topic novelty and growth simultaneously for their citation advantage in a future study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The novelty together with the volume of publications attract other researchers' attention and increase visibility and impact (Tu & Seng, 2012). We have not studied novelty in this paper but Thelwall and Sud (2021) found that articles published around novel topics have a citation advantage using a word frequency analysis. It would be interesting to study topic novelty and growth simultaneously for their citation advantage in a future study.…”
Section: Discussionmentioning
confidence: 92%
“…and fast growth together with novelty is predicted to lead to prominent impact in the future (Rotolo et al, 2015). Prior studies have already confirmed the association between novelty (newness) and citation impact and showed that new research has a citation advantage (Porter et al, 2019), although it may significantly vary across different subject domains (Thelwall & Sud, 2021).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Citing papers is a common way to express appreciation of someone else's research or to acknowledge the relevance thereof to our own results [1]. Regardless of the true motivation [2], the what-to-cite decisions of individual authors can be averaged over the whole bibliographic networks.…”
Section: Introductionmentioning
confidence: 99%